336 Prognostic Significance of Plasma Insulin Level for Deep Venous Thrombosis in Patients with Severe Traumatic Brain Injury in Critical Care. (April 2023) - Du, Min; Tang, Rui; Zhang, Qing-Hong; Liu, Haiyan; Ji, Zongsu; Zhou, Min
Abstract : INTRODUCTION: Whether insulin resistance is underlying the deep venous thrombosis (DVT) development in patients with traumatic brain injury (TBI) is elusive. METHODS: A prospective observational study of 73 severe TBI patients who had measurements of plasma insulin, glucose, glucagon-like peptide 1 (GLP-1), inflammatory factors, and hematological profile within 4 preset time periods during 2 weeks after TBI. Ultrasonic surveillance of DVT was tracked weekly. Two-way ANOVA analysis was applied to determine whether the factors could discriminate between patients with and without DVT. Partial correlations of insulin level with other variables were carried out in patients with or without DVT. Factors associated with DVT were analyzed by multivariable logistic regression. Neurological outcome 6 months after TBI was assessed for Glasgow Outcome Scale (GOS). RESULTS: Among patients with an average (SD) age of 53 ± 16 years, DVT developed in 20 patients (27%). The 14-day plasma insulin levels were higher in patients with DVT (P = 0.01). Platelet profile discriminated significantly between patients with and without DVT. None of other factors differed between the two groups. Patients with insulin therapy had significant higher insulin (P = 0.006), glucose (P < 0.001) and GLP-1 (P = 0.01) levels, and were more likely to develop DVT (60% vs. 15%, P < 0.001) with concomitant platelet depletion. Insulin levels correlated with glucose, GLP-1 levels, and platelet exclusively in patients without DVT. Conversely, in patients with DVT, insulin correlated negatively with GLP-1 level (r = -0.297, P = 0.016). Age (P = 0.01) and elevated insulin level at day 4-7 (P = 0.04) were independently associated with DVT. Patients with insulin therapy also showed worse GOS (P = 0.001). CONCLUSIONS: Elevated insulin level in the first 14 days after TBI may present insulin resistance in TBI, which was associated with consistent platelet activation, thus increasing risk of DVT.